Nasal polyposis in pediatric patients with Cornelia de Lange syndrome: endoscopic diagnosis, treatment and follow up in two case reports - Roberta Onesimo; Rita De Santis; Chiara Leoni; Mario Rigante; Marco Piastra; Elisabetta Sforza; Angelo Selicorni; Giuseppe Zampino (BMC, 2023)
Abstract Background Cornelia de Lange syndrome is a rare genetic disease with otolaryngological involvement. The classic phenotype is characterized by distinctive facial features, intellectual disability, growth delay, hirsutism, and upper-limb reduction. Nasal polyposis was previously reported in association with chronic rhinosinusitis, however data about prevalence, diagnosis, treatment and prognosis are lacking for this cohort of patients, affected by rare disease. Case presentation We describe the whole diagnostic and therapeutic workflow of nasal polyps in two pediatric patients with Cornelia de Lange, successfully diagnosed and treated by nasal endoscopy. Conclusion Our report confirm that nasal endoscopy is a safe and useful tool in the diagnosis, treatment and follow-up of nasal polyps, even in Cornelia de Lange syndrome pediatric patients. We want to increase the alert for the detection of nasal polyps in patients with Cornelia de Lange syndrome since pediatric age. We recommend endoscopy in all patients with Cornelia de Lange syndrome and symptoms of chronic nasal obstruction and/or OSAS. Multidisciplinary team and sedation service could be useful in the management of Cornelia de Lange syndrome patients with airway obstruction symptoms and sleep disturbance when severe intellectual disability, autism or psychiatric findings are present.